2017
DOI: 10.1021/acsami.7b03269
|View full text |Cite
|
Sign up to set email alerts
|

Which Oxide for Low-Emissivity Glasses? First-Principles Modeling of Silver Adhesion

Abstract: Density functional theory (DFT) calculations were performed to assess the work of adhesion of silver layers deposited on metal oxide surfaces differing by their chemical nature (ZnO, TiO, SnO, and ZrO) and their crystallographic face. The calculated work of adhesion values range from ∼0 to 3 J m and are shown to originate from the interplay between ionic (associated with charge transfer at the interface) and covalent (as probed by atomic bond orders between silver and the metal oxide atoms) interactions. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Many studies have already been made at the theoretical level to investigate the origin of interface adhesion and have demonstrated that this property is strongly connected to the formation of chemical bonds at the interface. Density functional theory (DFT) calculations made on ZnO, TiO 2 , SnO 2‑ , or ZrO 2 /metal interfaces have also shown that a weak work of adhesion is typically associated with a low interfacial charge transfer and vice versa . ,− This connection was also observed for other kinds of interfaces such as oxide/oxide or metal/carbide . Therefore, a fine control of the nature of the interface chemistry appears to be mandatory to obtain a strong adhesion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many studies have already been made at the theoretical level to investigate the origin of interface adhesion and have demonstrated that this property is strongly connected to the formation of chemical bonds at the interface. Density functional theory (DFT) calculations made on ZnO, TiO 2 , SnO 2‑ , or ZrO 2 /metal interfaces have also shown that a weak work of adhesion is typically associated with a low interfacial charge transfer and vice versa . ,− This connection was also observed for other kinds of interfaces such as oxide/oxide or metal/carbide . Therefore, a fine control of the nature of the interface chemistry appears to be mandatory to obtain a strong adhesion.…”
Section: Introductionmentioning
confidence: 98%
“…As a result, ZrO 2 could also prove to be a material of choice in low-emissivity glasses. However, our previous theoretical calculations indicate that the defect-free ZrO 2 (111)/Ag­(111) interface exhibits a very poor adhesion . The mechanical properties of heterogeneous materials depend mostly on the strength of adhesion between their components .…”
Section: Introductionmentioning
confidence: 98%
“…Beyond the argument of a reduced band gap compared to bulk-insulating oxides 3 and of a good crystallization during sputtering deposition, several fundamental reasons have been put forward to explain the enhanced adhesion on ZnO. 4 The first argument relies on the polarity of the (0001) orientation in the wurtzite structure 5 since the polycrystalline ZnO layers on which silver is deposited display a strong c-axis fiber texture. Among different mechanisms such as the creation of vacancies or hydroxylation, charge transfer to the deposited metal should allow to circumvent the polar catastrophe, i.e., the electrostatic divergence of the surface potential due to the alternate stacking of Zn cation and O anion planes along the [001] direction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the potential oxide substrates, ZnO wurtzite turned out to be one of the best candidates in terms of silver wetting. Beyond the argument of a reduced band gap compared to bulk-insulating oxides and of a good crystallization during sputtering deposition, several fundamental reasons have been put forward to explain the enhanced adhesion on ZnO …”
Section: Introductionmentioning
confidence: 99%
“…The principle structure of a Low-E coating is a reflective layer sandwiched between two dielectric layers. Typically a thin film of silver, grown by magnetron sputtering is used as the reflective layer, while zinc oxide is used as the dielectric layer 2 (however other dielectric materials have been investigated 3 ). It is this application of the Ag-ZnO interface that motivates the work described in this article.…”
Section: Introductionmentioning
confidence: 99%